Meliola Elaeocarpicola SP. Nov. (Ascomycetes, Meliolales) From Malabar Wildlife Sanctuary in Kerala State, India (Journal of Plant Disease Sciences, 2019)
A huge number of Meliolaceous fungi were reported from India and there was a requirement for the consolidation of this group, Hosagoudar (1996) did a Monographic study for India by including 6 genera and 378 species. However, the enthusiastic work on this group continued in Kerala by Hoasgoudar and Jacob Thomas (2013) contributed to Meliolales of Kerala and other southern parts of India; Hosagoudar (2008, 2013) for Meliolales of India and Hosagoudar and Agarwal (2008), for the world monograph are the subsequent works.
Keywords: Meliola elaeocarpaceae sp. Fungi; comparative features